Research on NiCr/NiSi thin film thermocouple sensor for measuring the surface temperature of automobile engine - Wang, Haochen (Frontiers in Materials, 2025)
This study describes a method for preparing thermocouple sensor based on NiCr/NiSi thin films. Using magnetron sputtering technology, the sensor structure includes a substrate, a SiO2 transition layer, a NiCr/NiSi thermocouple and a SiO2 protective layer.Experiments show that the sensor has a stable thermopotential output at 80°C with a Seebeck abrcoefficient of about 40.97μV/°C. By measuring the engine surface temperature of a Subaru Outback 2.5i car, the practicability of the sensor is verified. The 2 × 2 cm ceramic-based thermocouple used for automobile engine temperature measurement is the best choice to ensure the fast and stable operation of the temperature sensor. Experimental results show that this thermocouple achieved the highest temperature measurements of 72.85°C in comparison to other substrates, demonstrating its superior thermal conductivity and stability in high-temperature environments.